Constructing grounded theory - Charmaz, Kathy, 1939- (London ; Thousand Oaks, Calif. : SAGE, 2014)
Kathy Charmaz presents the definitive guide to doing grounded theory from a constructivist perspective. This second edition of her groundbreaking text retains the accessibility and warmth of the first edition whilst introducing cutting edge examples and practical tips.
An invitation to grounded theory -- Gathering rich data -- Crafting and conducting intensive interviews -- Interviewing in grounded theory studies -- The logic of grounded theory coding practices and initial coding -- Focused coding and beyond -- Memo-writing -- Theoretical sampling, saturation, and sorting -- Reconstructing theorizing in grounded theory studies -- Symbolic interactionism and grounded theory -- Writing the draft -- Reflecting on the research process.
Includes bibliographical references (p. [346]-378) and index.
Keywords: Grounded theory